Impacts of Application Light-Emitting Diode (LED) Lamps in Reducing Generator Power on Ro-Ro Passenger Ship 300 GT KMP Bambit - Suardi Suardi; Aung Ye Kyaw; Amalia Ika Wulandari; Fahmi Zahrotama (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2023)
KMP Bambit is an Indonesian Ro-Ro ship that carries passengers. It is public transportation from Merauke Regency to Asmat Regency and vice versa. The ship is still using fluorescent lamps as its main lighting source. This study presents a comparative study of the efficiency level between the use of fluorescent lamps and LED lamps in the room aboard the ship. The method used is the zonal cavity (lumen) method by dividing each room into three parts, namely the height ceiling cavity (hcc), height room cavity (hrc), and height floor cavity (hfc). The illumination value was determined according to the standards set for each room. The principal results for comparing lighting power on KMP Bambit showed that the total lighting electrical load accumulated using the fluorescent lighting type was 24.31kW. In contrast, LED lighting had a total lighting electrical load of 16.51 kW. This reduced the generator power from 68 kW to 60 kW, which could improve the efficiency of ship fuel operational costs. This study can evaluate the existing Ro-Ro ship fleet and be a good option in the process of building Ro-Roships in the future.